Peningkatan Kemampuan Komunikasi dan Self-Efficacy Siswa SMP dengan Menggunakan Pendekatan Diskursif - Marlina Marlina; M. Ikhsan; Yusrizal Yusrizal (Didaktik Matematika, 2014)
The ability of communication is one of the mathematical ability to be mastered by students in learning mathematics. Students who have good mathematical communication skills will be able to create a diverse representation in solving problem. This will facilitate the students in making a variety of alternative settlement so as to enhance the students' ability in solving mathematical problems. One of approach to learning that is likely to improve mathematical communication skills and self-efficacy students is discursive approach. This research is experimental research with quantitative approach. The aim is to obtain an increase in mathematical communication skills and self-efficacy of students by using a discursive approach is reviewed by the entire student and student grouping. This study used a pretest - posttest the control group. The data of mathematical communication ability collecting using test and the data of student self-efficacy collecting by questionnaire. Based on the analysis, it can be concluded that the improvement of students' mathematical communication skills are taught using a discursive approach is better than the improvement of students' mathematical communication skills are taught using the conventional approach based on the students' overall well-reviewed and reviewed based on level students. For self-efficacy concluded that there are differences increase in self-efficacy between students taught with the discursive approach better than students who were taught using the conventional approach. Based on the analysis concluded that there is an interaction between the factors of teaching approach and leveling students with.The improvement of students' mathematical communication skills while learning approach to factors and level of students to self-efficacy of students there is no interaction.